2006
DOI: 10.1002/rcm.2648
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectral characterization of ergot alkaloids by electrospray ionization, hydrogen/deuterium exchange, and multiple stage mass spectrometry: usefulness of precursor ion scan experiments

Abstract: Six ergot alkaloids belonging to the lysergic acid derivatives (ergonovine (EGN) and methysergide hydrogen maleinate (MHM)) and peptide-type derivatives (ergocristine (EGR), ergotamine (EGT), ergocornine (EGC) and alpha-ergokryptine (EGK)) were studied by positive electrospray tandem mass spectrometry. The fragmentation mechanisms of these compounds were studied by collision-induced dissociation (CID) using triple quadrupole and ion trap mass spectrometers, and the nature of the major product ions further conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
3
23
1
Order By: Relevance
“…Five A+2 isotopes, including ergometrine, the ergot alkaloid in this study with the lowest molecular weight, could not be detected at 1 ng/mL. In contrast, ochratoxin A, the only mycotoxin in this study consisting of 35 Cl and 37 Cl isotopes, produced a fourth molecular isotope that could be reliably identified at all three concentration levels. Table 3.…”
Section: ■ Results and Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Five A+2 isotopes, including ergometrine, the ergot alkaloid in this study with the lowest molecular weight, could not be detected at 1 ng/mL. In contrast, ochratoxin A, the only mycotoxin in this study consisting of 35 Cl and 37 Cl isotopes, produced a fourth molecular isotope that could be reliably identified at all three concentration levels. Table 3.…”
Section: ■ Results and Discussioncontrasting
confidence: 72%
“…The use of Q-orbital trap MS technology has been evaluated thoroughly by applying a validation for mycotoxins in grain and nut products comparable to a previous LC-MS/MS study, evaluating reference and actual food samples, and providing high-accuracy mass fragmentation information that was useful for mycotoxin identification. Future research will include 30 and Mohammed et al 31 with experimental agreement and some modifications by studies performed in this work as well as by Mulac et al 32 and Arroyo-Manzanares et al 35 If protonation occurs at the amide bond 1A, two fragmentation pathways (A,B) are possible: (A) α-cleavage of the amide bond to form 3A, 3B, or (B) β-cleavage of the amide bond in 2, which can lose NH 3 to form 3A, 3B. Structures 3A, 3B can either lose CO to 5 or undergo rearrangement to 4.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…2014; Mohamed et al, 2006b) and indicated that all derivatives give rise mainly to fragment ions with m/z 223 and 208 corresponding to the four-ring system of the lysergic moiety and its demethylated counterpart, respectively. In total, 19 different compounds demonstrated a fragmentation pattern that pointed to ergot alkaloids.…”
Section: Screening and Identification Of Unknown And Less Studied Ergmentioning
confidence: 99%
“…Analytical methods for the determination of ergot alkaloids include thin layer chromatography (TLC) (Salvat and Godoy, 2001), capillary electrophoresis (CE) (Franch and Blaschke, 1998), enzyme linked immunosorbent assay (ELISA) (Hill et al, 2001), gas chromatography (GC) with electron capture detection (ECD) (Barrow and Quigley, 1975), liquid chromatography (LC) with ultraviolet (Veress, 1993), fluorescence (Komarova and Tolkachev, 2001a;Storm et al, 2008) or mass spectrometric (MS) (Diana di Mavungu et al, 2012;Burk et al, 2006;Kokkonen and Jestoi, 2010;Krska et al, 2008a;Mohamed et al, 2006b) detection. Over the last decade, LC-MS has become a dominant tool for mycotoxin determination, and has provided an unequivocal identification of ergot alkaloids in various matrices (Diana di Mavungu et al, 2012;Friedrich et al, 2004;Kokkonen and Jestoi, 2009;Krska et al, 2008;Lehner et al, 2005;Mohamed et al, 2006a;Mohamed et al, 2006b). Due to its simple operation and low cost, ergot alkaloid analysis is currently mainly conducted using a triple-quadrupole (QqQ) MS system.…”
Section: Introductionmentioning
confidence: 99%